High-hydrophilicity nano composite functional fiber membrane for alkaline electrolyzed water and preparation method of high-hydrophilicity nano composite functional fiber membrane

A nano-composite functional fiber membrane for alkaline water electrolysis is developed by using a polyphenylene sulfide-based intermediate layer with inorganic nanoparticles and hydrophilic treatment, addressing hydrophilicity and gas barrier issues, resulting in improved performance and stability.

CN119215671APending Publication Date: 2024-12-31ZHEJIANG UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411384379.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

Existing polyphenylene sulfide diaphragms for alkaline water electrolysis suffer from poor hydrophilicity and gas barrier properties, leading to high resistance and instability during use.

Method used

A nano-composite functional fiber membrane is prepared using a polyphenylene sulfide-based membrane as an intermediate layer, combined with inorganic nanoparticles, polymers, and organic solvents, and subjected to hydrophilic treatment and double-sided coating to enhance ion conductivity and gas barrier properties.

Benefits of technology

The membrane exhibits improved hydrophilicity, air tightness, high temperature resistance, and corrosion resistance, with reduced surface resistance and enhanced mechanical properties compared to existing diaphragms.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119215671A_ABST
    Figure CN119215671A_ABST
Patent Text Reader

Abstract

The invention discloses a high-hydrophilicity nano composite functional fiber membrane for alkaline electrolyzed water and a preparation method of the high-hydrophilicity nano composite functional fiber membrane. The preparation method comprises the following steps: taking a polyphenylene sulfide fiber base membrane as a middle layer, mixing inorganic nanoparticles with different particle sizes, a polymer, a pore-foaming agent and an organic solvent to prepare a membrane casting solution, carrying out hydrophilization treatment on the polyphenylene sulfide base membrane, and carrying out double-sided coating (or single-sided coating) on the polyphenylene sulfide base membrane by using the membrane casting solution, so as to obtain the composite membrane. And finally, curing the membrane casting solution into the membrane through pre-evaporation and non-solvent phase conversion. Through the polyphenylene sulfide base membrane with high porosity, low resistance, relatively strong mechanical strength, dimensional stability, good smoothness and stiffness and relatively good hydrophilicity, the surface hydrophilicity of the diaphragm after double-sided (or single-sided) coating is good, and the aperture of the diaphragm is reduced through compounding of multi-particle-size inorganic nanoparticles, so that the gas barrier property is obviously improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing a nano composite functional fiber membrane for alkaline water electrolysis, and in particular to a method for preparing a high temperature resistant, corrosion resistant, highly hydrophilic and highly gas barrier diaphragm. Background Art

[0002] Fossil energy is the key energy source for human survival, but with the increasingly serious energy crisis and accompanied by environmental pollution problems, humans are constantly looking for new energy structures to achieve the goal of "carbon neutrality". Hydrogen energy, as a new energy source, has the advantages of being green, clean, efficient, and widely available. It will become a mainstream energy supply method in the future. Compared with other hydrogen production methods, water electrolysis hydrogen production technology does not cause pollution and is a hydrogen production technology that has received widespread attention.

[0003] Water electrolysis technology includes alkaline water electrolysis, proton exchange membrane water electrolysis, anion exchange membrane water electrolysis, and solid oxide water electrolysis. Alkaline water electrolysis technology is the most mature water electrolysis technology. It has been promoted and applied to a certain extent because of its simple operation, low cost, good stability, and ability to be used in large-scale hydrogen production.

[0004] Asbestos diaphragm was the earliest alkaline water electrolysis diaphragm used, but due to its poor conductivity, it will produce high diaphragm resistance, is easily corroded and swollen by alkaline electrolyte, and is carcinogenic to the human body, so it has gradually been replaced by other separation materials; polyphenylene sulfide woven fabrics and polyphenylene sulfide non-woven fabrics have gradually become a mainstream alkaline water electrolysis diaphragm. Polyphenylene sulfide has good alkali resistance and thermal stability, and polyphenylene sulfide ultrafine fibers have a larger specific surface area, lower bending stiffness, higher fiber monofilament specific strength and flexibility, but due to the poor hydrophilicity of polyphenylene sulfide, during use, more bubbles will adhere to the surface of the diaphragm, resulting in a large resistance. At the same time, its porosity is high, the gas barrier property is poor, and the stability during use needs to be further improved. How to improve the hydrophilicity and gas barrier properties of polyphenylene sulfide diaphragms is the key issue in applying polyphenylene sulfide diaphragms to electrolysis water. At present, the composite of multiple materials has become an important development direction of alkaline water electrolysis diaphragms.

[0005] In view of a series of problems existing in polyphenylene sulfide woven fabric diaphragms, it is urgent to develop an alkaline water electrolysis diaphragm that is both resistant to high temperature and corrosion and has high hydrophilicity and air tightness. Summary of the invention

[0006] The purpose of the present invention is to solve the problem of poor hydrophilicity and air tightness of the existing polyphenylene sulfide diaphragms, and to provide a nano-composite functional fiber membrane for alkaline water electrolysis with high hydrophilicity, air tightness, high temperature resistance and corrosion resistance. The method obtains a polyphenylene sulfide-based membrane intermediate layer with certain mechanical strength, good stiffness, good dimensional stability, high temperature resistance and corrosion resistance by a wet method or a dry method, and performs a hydrophilic treatment on it to improve its ion conductivity and compatibility with the casting liquid, and performs a double-sided (single-sided) hydrophilic casting liquid coating on it to improve the comprehensive performance of the diaphragm, so that it has better hydrophilicity and air tightness than polyphenylene sulfide diaphragms, and has better mechanical properties and high temperature resistance and corrosion resistance and lower resistance than polysulfone / zirconia diaphragms.

[0007] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention is:

[0008] A nano composite functional fiber membrane for alkaline water electrolysis, the preparation method of which is as follows: inorganic nano particles of different particle sizes, polymers, porogens, and organic solvents are mixed to obtain a casting solution, a polyphenylene sulfide-based membrane is used as an intermediate layer of the nano functional fiber composite membrane, and the membrane is subjected to a hydrophilic treatment to improve its ion conductivity and compatibility with the casting solution, the polyphenylene sulfide-based membrane is fixed, the casting solution is scraped on one side by a scraping machine, and the casting solution is solidified by pre-evaporation and non-solvent phase conversion, and the above operation is repeated on the other side of the polyphenylene sulfide-based membrane to obtain the nano functional fiber composite membrane.

[0009] The effects of different fiber ratios in polyphenylene sulfide-based membranes and the thickness of the polyphenylene sulfide layer on the performance of the diaphragm were systematically studied. The ratio of inorganic nanoparticles of different particle sizes was optimized to improve their dispersibility and the pore structure of the diaphragm. The scraping process conditions of the casting liquid on the polyphenylene sulfide layer were optimized to achieve the effect of nano-functional fiber composite membrane materials with hydrophilicity, gas barrier properties, high temperature resistance, corrosion resistance, and excellent mechanical properties.

[0010] A method for preparing a modified nanocomposite diaphragm for alkaline water electrolysis with high hydrophilicity, the method comprising the following steps:

[0011] (1) Preparation of casting solution

[0012] The polymer is added to the organic solvent in batches, the solution is added to the homogenizer, the speed is adjusted to 500-1000rpm, and then inorganic nanoparticles of different particle sizes and porogens are added step by step, and after stirring for 2-12h, the obtained slurry is ultrasonically treated for 0.5-1h to obtain a milky white casting solution. The mass ratio of the polymer to the inorganic nanoparticles is (1:9)-(2:3), preferably (1:8.5)-(1:4), the inorganic nanoparticles have a particle size of 200nm-400nm accounting for 50%-90%, preferably 60%-70%, the mass ratio of the organic solvent in the casting solution is 30%-70%, preferably 45%-55%, and the mass ratio of the porogen in the casting solution is 0.1%-5%, preferably 0.5%-2%.

[0013] (2) Selection of polyphenylene sulfide base film

[0014] The polyphenylene sulfide base film selected for the intermediate layer is obtained by wet or dry forming a sheet-like base film from polyphenylene sulfide staple fibers or polyphenylene sulfide pulp, drying, hot pressing, and then hydrophilic treatment; the polyphenylene sulfide staple fibers are selected to have a fineness of 0.89D to 3.2D and a length of 3 to 8 mm. The thickness of the polyphenylene sulfide base film is selected to be 50 μm to 300 μm, preferably 60 μm to 120 μm. The polyphenylene sulfide membrane is subjected to a hydrophilic treatment, and the hydrophilic treatment method includes sulfuric acid sulfonation, nitric acid nitration, oxygen plasma treatment, and glacial acetic acid hydrogen peroxide oxidation, preferably glacial acetic acid hydrogen peroxide oxidation.

[0015] (3) Preparation of nano-functional fiber composite membrane

[0016] The polyphenylene sulfide film base film is fixed with a mold, the casting liquid is poured on one side of the glass polyphenylene sulfide base film, and the casting liquid is scraped on one side with a scraping machine to scrape out a wet film with a thickness of 50 to 1000 μm, the pre-evaporation time is 10s to 240s, preferably 120s to 180s, the non-solvent phase conversion temperature is 5°C to 25°C, preferably 10°C to 15°C, after the phase conversion is completed, it is taken out from the coagulation bath, and soaked in water for many times, the residual solvent is cleaned, and it is naturally dried, and cut to obtain a nano-functional fiber composite membrane for alkaline water electrolysis. The final surface coating layer thickness is 30μm to 300μm, preferably 60μm to 120μm.

[0017] The polymer is one or more of polysulfone, polyethersulfone, polyphenylsulfone, polystyrene, polyimide, polyethylene, and polypropylene, wherein polysulfone is preferred, and the molecular weight is 20,000 to 100,000, preferably 40,000 to 80,000. The porogen is selected from PVP K30 or PVP K90. The organic solvent is selected from one or more of N-methylpyrrolidone (NMP), N-ethylpyrrolidone (NEP), N-butylpyrrolidone (NBP), dimethyl sulfoxide (DMSO), acetone, xylene, toluene, and N,N-dimethylformamide (DMF), preferably one of N-methylpyrrolidone (NMP), N-ethylpyrrolidone (NEP), and N-butylpyrrolidone (NBP).

[0018] The inorganic nanoparticles are one or more of nano-zirconium oxide, nano-titanium oxide, nano-zinc oxide, nano-copper oxide, nano-aluminum oxide, nano-cerium oxide, and nano-silicon oxide, among which nano-zirconium oxide is preferred.

[0019] Compared with the prior art, the excellent effects of the present invention are embodied in:

[0020] (1) When preparing the casting solution, inorganic nanoparticles of different particle sizes are used to reduce the average pore size of the diaphragm to improve the gas barrier property of the diaphragm. At the same time, it can effectively inhibit the agglomeration of inorganic nanoparticles at high content, improve the dispersion and uniformity of the surface layer of the diaphragm, and maintain excellent hydrophilicity.

[0021] (2) The base film production process is simple and easy to industrialize. At the same time, the polyphenylene sulfide base film can provide good high temperature resistance and corrosion resistance for the diaphragm. It also has certain mechanical strength, good dimensional stability, and good stiffness, which can provide excellent coating processing performance for the coating process. It also has low resistance.

[0022] (3) The membrane making process is relatively simple. After the polyphenylene sulfide-based membrane is coated with a hydrophilic casting liquid on both sides (one side), the hydrophilicity and air tightness of the membrane can be improved, making it have better hydrophilicity and gas barrier properties than polyphenylene sulfide membranes, and better mechanical properties, high temperature corrosion resistance and lower resistance than polysulfone / zirconia membranes. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 It is a schematic diagram of the diaphragm made by this design method.

[0024] Figure 2 This is an electron microscope image of the diaphragm produced by single-sided coating. Specific implementation methods

[0025] The present invention is further described below in conjunction with specific embodiments, but the protection scope of the present invention is not limited thereto.

[0026] like Figure 1 and 2 As shown, the present invention provides a method for preparing a nano-functional fiber composite membrane for alkaline water electrolysis. The present invention uses a polyphenylene sulfide fiber-based membrane as an intermediate layer, and uses inorganic nanoparticles of different particle sizes, polymers, porogens, and organic solvents to prepare a casting liquid. After the polyphenylene sulfide-based membrane is hydrophilized, the polyphenylene sulfide-based membrane is double-sidedly coated (or single-sidedly coated) with the casting liquid, and finally the casting liquid is solidified into a membrane through pre-evaporation and non-solvent phase conversion. The present invention uses a polyphenylene sulfide-based membrane with high porosity, low resistance, strong mechanical strength, dimensional stability, good flatness and stiffness, and good hydrophilicity. The surface of the diaphragm has good hydrophilicity after double-sided (or single-sided) coating, and the diaphragm pore size is reduced by composite inorganic nanoparticles with multiple particle sizes, so that the gas barrier property is significantly improved. As Figure 2 Shown is an electron microscope image of the single-sided coated diaphragm.

[0027] Example 1

[0028] 3 g of polysulfone was added to 20 g of N-methylpyrrolidone in two portions, the speed of the homogenizer was adjusted to 1000 rpm, and then 0.4 g of PVP K30, 10.2 g of 200 nm to 400 nm nano ZrO2 particles, and 6.8 g of nano ZrO2 particles less than 100 nm were added, stirred for 20 min, and the obtained slurry was ultrasonically treated for 1 h.

[0029] 4.5g 3.2D*8mm polyphenylene sulfide staple fibers, 3g 0.89D*6mm polyphenylene sulfide staple fibers and 5g polyphenylene sulfide pulp fibers were wet-formed into a sheet-like base film, which was dried, hot-pressed and hydrophilically treated to obtain a polyphenylene sulfide base film.

[0030] After the polyphenylene sulfide-based membrane is subjected to oxidation reaction with glacial acetic acid and hydrogen peroxide for 1 hour, it is fixed with a mold, and the casting liquid is poured on one side of the glass polyphenylene sulfide-based membrane. The casting liquid is scraped on one side with a scraper to scrape out a wet film with a thickness of 250 μm. The membrane is pre-evaporated for 120 seconds and added into a 15°C coagulation bath for phase inversion. After the phase inversion is completed, it is taken out from the coagulation bath, and the above operation is repeated on the other side of the polyphenylene sulfide-based membrane. The membrane is immersed in water for multiple times to clean the residual solvent, dry naturally, and cut to obtain a nano-functional fiber composite membrane for alkaline water electrolysis.

[0031] Comparative Example 1

[0032] 3 g of polysulfone was added to 20 g of N-methylpyrrolidone in two portions, the speed of the homogenizer was adjusted to 1000 rpm, and then 0.4 g of PVP K30, 10.2 g of 200 nm to 400 nm nano ZrO2 particles, and 6.8 g of nano ZrO2 particles less than 100 nm were added, stirred for 20 min, and the obtained slurry was ultrasonically treated for 1 h.

[0033] A 40-mesh polyphenylene sulfide grid was fixed with a mold, and the casting liquid was poured on one side of the glass polyphenylene sulfide grid. The casting liquid was scraped on one side with a scraper to scrape out a wet film with a thickness of 750 μm. The film was pre-evaporated for 120 seconds and added into a 15°C coagulation bath for phase inversion. After the phase inversion was completed, the film was taken out from the coagulation bath and immersed in water for multiple times to clean the residual solvent. The film was dried naturally and cut to obtain a nano-functional fiber composite membrane for alkaline water electrolysis.

[0034] Comparative Example 2

[0035] 3 g of polysulfone was added to 20 g of N-methylpyrrolidone in two portions, the speed of the homogenizer was adjusted to 1000 rpm, and then 0.4 g of PVP K30 and 17 g of 200 nm to 400 nm nano ZrO2 particles were added, stirred for 20 min, and then the obtained slurry was ultrasonically treated for 1 h.

[0036] 4.5g 3.2D*8mm polyphenylene sulfide staple fibers, 3g 0.89D*6mm polyphenylene sulfide staple fibers and 5g polyphenylene sulfide pulp fibers were wet-formed into a sheet-like base film, which was dried, hot-pressed and hydrophilically treated to obtain a polyphenylene sulfide base film.

[0037] After the polyphenylene sulfide-based membrane was oxidized with glacial acetic acid and hydrogen peroxide for 1 hour, it was fixed with a mold, and the casting liquid was poured on one side of the glass polyphenylene sulfide-based membrane. The casting liquid was scraped on one side with a scraper to scrape out a wet film with a thickness of 250 μm. The membrane was pre-evaporated for 120 seconds and added into a 15°C coagulation bath for phase inversion. After the phase inversion was completed, it was taken out from the coagulation bath, and the above operation was repeated on the other side of the polyphenylene sulfide-based membrane. The membrane was immersed in water for many times to clean the residual solvent, dried naturally, and cut to obtain a nano-functional fiber composite membrane for alkaline water electrolysis.

[0038] Example 2

[0039] 3 g of polysulfone was added to 20 g of N-methylpyrrolidone in two portions, the speed of the homogenizer was adjusted to 500 rpm, and then 0.4 g of PVP K90, 11.9 g of 200 nm to 400 nm nano ZrO2 particles, and 5.1 g of nano ZrO2 particles less than 100 nm were added, stirred for 20 min, and the obtained slurry was ultrasonically treated for 1 h.

[0040] 4.5g 3.2D*8mm polyphenylene sulfide staple fibers, 3g 0.89D*6mm polyphenylene sulfide staple fibers and 5g polyphenylene sulfide pulp fibers were wet-formed into a sheet-like base film, which was dried, hot-pressed and hydrophilically treated to obtain a polyphenylene sulfide base film.

[0041] After the polyphenylene sulfide-based membrane is treated with oxygen plasma hydrophilization, it is fixed with a mold, and the casting liquid is poured on one side of the glass polyphenylene sulfide-based membrane. The casting liquid is scraped on one side of the glass polyphenylene sulfide-based membrane with a film scraper to scrape out a wet film with a thickness of 250 μm. The membrane is pre-evaporated for 150 seconds and added into a 15°C coagulation bath for phase inversion. After the phase inversion is completed, it is taken out from the coagulation bath, and the above operation is repeated on the other side of the polyphenylene sulfide-based membrane. The membrane is immersed in water for multiple times to clean the residual solvent, dry naturally, and cut to obtain a nano-functional fiber composite membrane for alkaline water electrolysis.

[0042] Example 3

[0043] 3 g of polysulfone was added to 15 g of N-methylpyrrolidone in two portions, the speed of the homogenizer was adjusted to 1000 rpm, and then 0.6 g of PVPK30, 7.2 g of 200 nm to 400 nm nano ZrO2 particles, and 4.8 g of nano ZrO2 particles less than 100 nm were added, stirred for 15 min, and the obtained slurry was ultrasonically treated for 0.5 h.

[0044] 4.5g 3.2D*8mm polyphenylene sulfide staple fibers, 3g 0.89D*6mm polyphenylene sulfide staple fibers and 5g polyphenylene sulfide pulp fibers were wet-formed into a sheet-like base film, which was dried, hot-pressed and hydrophilically treated to obtain a polyphenylene sulfide base film.

[0045] After the polyphenylene sulfide-based membrane is treated with 98% H2SO4 sulfonation for 12 hours, it is fixed with a mold, and the casting liquid is poured on one side of the glass polyphenylene sulfide-based membrane. The casting liquid is scraped on one side with a scraper to scrape out a wet film with a thickness of 250 μm. The membrane is pre-evaporated for 180 seconds and added into a 15°C coagulation bath for phase inversion. After the phase inversion is completed, it is taken out from the coagulation bath, and the above operation is repeated on the other side of the polyphenylene sulfide-based membrane. The membrane is immersed in water for many times to clean the residual solvent, dry naturally, and cut to obtain a nano-functional fiber composite membrane for alkaline water electrolysis.

[0046] Example 4

[0047] 3 g of polysulfone was added to 30 g of N-methylpyrrolidone in two portions, the speed of the homogenizer was adjusted to 1000 rpm, and then 0.2 g of PVP K90, 10.2 g of 200 nm to 400 nm nano ZrO2 particles, and 6.8 g of nano ZrO2 particles less than 100 nm were added, stirred for 20 min, and the obtained slurry was ultrasonically treated for 0.5 h.

[0048] 6g of 3.2D*8mm polyphenylene sulfide staple fibers, 2.57g of 0.89D*6mm polyphenylene sulfide staple fibers and 7.01g of polyphenylene sulfide pulp fibers were wet-formed into a sheet-like base film, which was dried, hot-pressed and hydrophilically treated to obtain a polyphenylene sulfide base film.

[0049] After the polyphenylene sulfide-based membrane is nitrated with 30% HNO3 for 12 hours, it is fixed with a mold, and the casting liquid is poured on one side of the glass polyphenylene sulfide-based membrane. The casting liquid is scraped on one side with a film scraper to scrape out a wet film with a thickness of 250 μm. The membrane is pre-evaporated for 120 seconds and added into a 15°C coagulation bath for phase inversion. After the phase inversion is completed, it is taken out from the coagulation bath and immersed in water for multiple times to clean the residual solvent, dry naturally, and cut to obtain a nano-functional fiber composite membrane for alkaline water electrolysis.

[0050] Example 5

[0051] 3 g of polysulfone was added to 20 g of N-methylpyrrolidone in two portions, the speed of the homogenizer was adjusted to 1000 rpm, and then 0.6 g of PVP K30, 10.2 g of 200 nm to 400 nm nano ZrO2 particles, and 6.8 g of nano ZrO2 particles less than 100 nm were added, stirred for 15 min, and the obtained slurry was ultrasonically treated for 1 h.

[0052] 4.5g 3.2D*8mm polyphenylene sulfide staple fibers, 3g 0.89D*6mm polyphenylene sulfide staple fibers and 5g polyphenylene sulfide pulp fibers were wet-formed into a sheet-like base film, which was dried, hot-pressed and hydrophilically treated to obtain a polyphenylene sulfide base film.

[0053] After the polyphenylene sulfide base film was treated with plasma hydrophilization, it was fixed with a mold, and the casting liquid was poured on one side of the glass polyphenylene sulfide base film. The casting liquid was scraped on one side with a film scraper to scrape out a wet film with a thickness of 500 μm. The film was pre-evaporated for 90 seconds and placed in a 15°C coagulation bath for phase inversion. After the phase inversion was completed,

[0054] It is taken out from the coagulation bath, and the above operation is repeated on the other side of the polyphenylene sulfide-based membrane, and then immersed in water for multiple times to clean the residual solvent, dry naturally, and cut to obtain a nano-functional fiber composite membrane for alkaline water electrolysis.

[0055] Table 1 Comparison of test results of Examples 1 to 5:

[0056]

[0057] Table 2 Comparison of test results of Examples 1 to 5:

[0058]

[0059] As shown in Tables 1 and 2, compared with Comparative Example 1 using polyphenylene sulfide grid as the intermediate layer, Example 1 has certain improvements in air tightness and membrane resistance, and the overall performance is improved, because it uses a wet-made polyphenylene sulfide membrane as the intermediate layer, which has a high porosity and can provide excellent mechanical properties, and can maintain the membrane strength at a lower thickness. Compared with Comparative Example 2 that does not use multi-particle composite, Example 1 has a significantly reduced surface resistance of the membrane, and the multi-particle composite improves the pore structure of the membrane and improves the water absorption and permeability of the membrane. The membranes prepared by the ratios used in Example 1 and Example 2 have good comprehensive performance and have good prospects in alkaline water electrolysis applications.

[0060] In summary, the polyphenylene sulfide-based membrane is prepared by wet papermaking as the middle layer, and multi-size inorganic nanoparticles are used in the casting solution, and the middle layer is double-sided coated to form a phase-converted membrane. The diaphragm prepared by this method has high temperature resistance and corrosion resistance, and has high hydrophilicity and air tightness. It has good application prospects in alkaline electrolysis of water.

Claims

1. A method for preparing a nano-functional fiber composite membrane for alkaline water electrolysis, characterized in that: Inorganic nanoparticles of different particle sizes, polymers, porogens and organic solvents are mixed to prepare a casting solution, a polyphenylene sulfide-based membrane is used as the intermediate layer of the nano-functional fiber composite membrane, and the polyphenylene sulfide-based membrane is hydrophilized, the prepared casting solution is coated on one side of the polyphenylene sulfide-based membrane, the casting solution is solidified by pre-evaporation and non-solvent phase conversion, and the above operation is repeated on the other side of the polyphenylene sulfide membrane to obtain a nano-functional fiber composite membrane.

2. The method for preparing the nano-functional fiber composite membrane for alkaline water electrolysis according to claim 1, characterized in that: The inorganic nanoparticles are composited with multiple particle sizes, with particle sizes of 200nm to 400nm and particle sizes less than 100nm.

3. The method for preparing the nano-functional fiber composite membrane for alkaline water electrolysis according to claim 2, characterized in that: Among the composite inorganic nanoparticles, particles with a particle size of 200nm to 400nm account for 50% to 90%.

4. The method for preparing the nano-functional fiber composite membrane for alkaline water electrolysis according to claim 2, characterized in that: Among the composite inorganic nanoparticles, particles with a diameter of 200nm to 400nm account for 60% to 70%.

5. The method for preparing the nano-functional fiber composite membrane for alkaline water electrolysis according to claim 1, 2, 3 or 4, characterized in that: The mass ratio of the polymer to the inorganic nanoparticles is (1:9) to (2:3), preferably (1:8.5) to (1:4).

6. The method for preparing the nano-functional fiber composite membrane for alkaline water electrolysis according to claim 5, characterized in that: The polyphenylene sulfide base film used in the middle layer is obtained by wet or dry forming polyphenylene sulfide staple fibers or polyphenylene sulfide pulp into a sheet-like base film, drying, heat-pressing and then hydrophilic treatment.

7. The method for preparing the nano-functional fiber composite membrane for alkaline water electrolysis according to claim 6, characterized in that: The fineness of polyphenylene sulfide staple fibers is 0.89D to 3.2D, and the length is 3 to 8 mm.

8. The method for preparing the nano-functional fiber composite membrane for alkaline water electrolysis according to claim 6, characterized in that: The thickness of the polyphenylene sulfide base film is selected to be 30 μm to 300 μm.

9. The method for preparing the nano-functional fiber composite membrane for alkaline water electrolysis according to claim 6, 7 or 8, characterized in that: The thickness of the surface coating layer of the finally obtained nano-functional fiber composite membrane is 10 μm to 300 μm.

10. The method for preparing the nano-functional fiber composite membrane for alkaline water electrolysis according to claim 1, characterized in that The inorganic nanoparticles are one or more of nano zirconium oxide, nano titanium oxide, nano zinc oxide, nano copper oxide, nano aluminum oxide, nano cerium oxide, and nano silicon oxide.

Citation Information

Cited By

  • Alkaline electrolytic hydrogen diaphragm and production method thereof

    CN119392304A